2014
DOI: 10.1186/s12935-014-0072-1
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β isoforms induce EMT independent migration of ovarian cancer cells

Abstract: BackgroundTransforming growth factor beta (TGF-β) plays major roles in tumorigenesis by regulating cell growth, epithelial-to-mesenchymal transition (EMT), migration/invasion and metastasis. The epithelial markers E-cadherin, claudin-3 and claudin-4, commonly decreased in human adenocarcinomas are actually up regulated during ovarian carcinogenesis. In human ovarian cancer TGF-β1 may either suppress or promote tumor progression, but whether other TGF-β isoforms (TGF-β2 and TGF-β3) exert similar effects is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 34 publications
3
70
0
2
Order By: Relevance
“…TGF-β is synthesized as an inactive form by various cells, such as epithelial, hematopoietic, and neuronal cells [9]. TGF-β super family signaling mediators are important regulators of diverse physiological and pathological events [10][11][12]. Several pathways, involving many downstream proteins, mediate the effects of TGF-β1.…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β is synthesized as an inactive form by various cells, such as epithelial, hematopoietic, and neuronal cells [9]. TGF-β super family signaling mediators are important regulators of diverse physiological and pathological events [10][11][12]. Several pathways, involving many downstream proteins, mediate the effects of TGF-β1.…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian TGF isoforms (TGF-β1, TGF-β2 and TGF-β3) share 97% amino acid sequence identity and signal through activation of TGF-β receptors (28). TGF-β isoforms play major roles in tumourigenesis mediated by the EMT through regulating cell growth, migration, invasion and metastasis (28,37,38). Although pathway analyses should be mandatory to further identify the involvement PRMT5 in EMT process, our present results might suggest that PRMT5 partially participate in EMT programs through its coordinate expression with other EMT-inducing molecules in GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since elucidating the underlying mechanisms of metastasis occurred during the progression of EOC will make significant contributions toward combating this disease, a number of studies have identified several crucial regulators in the EMT, such as miR-125a, the miR-200 family of microRNAs (miR-141, miR-200a, b, c, and miR-429), miR-34, miR-205, zinc finger E-box binding homeobox 1 (ZEB1) and zinc finger E-box binding homeobox 2 (ZEB2) [11][12][13][14][15]. Especially, the plasma miR-205 has been indicated as a biomarker for ovarian cancer detection that complement CA-125, and the upregulation of miR-205 has also been reported to promote the invasion and proliferation of ovarian cancer cells [16]; ZEB1 has been identified as an activator of EMT in EOC cells [17], and the regulatory effect of miR-205 on ZEB1 expression has been confirmed based on various cancer cells, including breast cancer cells and papillary urothelial tumors of the urinary bladder [18,19].…”
Section: Accepted Manuscriptmentioning
confidence: 99%